Hubungan Work Life Balance dan Self Efficacy dengan Organizational Citizenship Behavior pada Karyawan - Marsella Margaretha; Diah Sofiah; Yanto Prasetyo (JIWA: Jurnal Psikologi Indonesia, 2025)
AbstractCompanies currently are facing the challenge of improving organizational performance through more proactive employee behaviors, such as Organizational Citizenship Behavior, which not only depends on the achievement of primary tasks but also on additional contributions that benefit the organization. Several factors are believed to influence Organizational Citizenship Behavior, such as Work Life Balance and Self Efficacy. However, the relationship between these three factors has not been extensively explored, particularly within the context of organizations in Indonesia. Organizational Citizenship Behavior is one form of voluntary behavior that is highly beneficial to companies. Using a quantitative approach, data was collected from employees as respondents. The results of the study indicate a significant relationship between Work Life Balance and Self Efficacy with Organizational Citizenship Behavior. Employees with a high level of Work Life Balance tend to have higher Self Efficacy, which in turn increases the likelihood of exhibiting Organizational Citizenship Behavior. Data analysis was conducted using multiple linear regression to examine the relationships between variables. The results show that both Work Life Balance and Self Efficacy have a strong positive relationship with Organizational Citizenship Behavior (R = 0.694, p < 0.05). Overall, this study suggests that companies should maintain a positive work environment to ensure that levels of Work Life Balance, Self Efficacy, and Organizational Citizenship Behavior among employees remain high.Keywords: Organizational Citizenship Behavior, Self Efficacy, Work Life BalanceAbstrakPerusahaan saat ini menghadapi tantangan dalam meningkatkan kinerja organisasi melalui perilaku yang lebih proaktif dari karyawan, seperti Organizational Citizenship Behavior, yang tidak hanya bergantung pada pencapaian tugas utama, tetapi juga kontribusi tambahan yang bermanfaat bagi organisasi. Beberapa faktor yang diduga mempengaruhi Organizational Citizenship Behavior adalah Work Life Balance serta Self Efficacy. Namun, hubungan antara ketiga faktor ini belum banyak dieksplorasi secara mendalam, khususnya dalam konteks organisasi di Indonesia. Organizational Citizenship Behavior merupakan salah satu bentuk perilaku sukarela yang sangat menguntungkan bagi perusahaan. Melalui pendekatan kuantitatif, data dikumpulkan dari responden yang merupakan karyawan. Hasil penelitian menunjukkan bahwa terdapat hubungan signifikan antara Work Life Balance dan Self Efficacy dengan Organizational Citizenship Behavior. Karyawan dengan Work Life Balance yang tinggi cenderung memiliki Self Efficacy yang lebih tinggi pula, sehingga meningkatkan kecenderungan munculnya perilaku Organizational Citizenship Behavior. Analisis data dilakukan menggunakan regresi linier berganda untuk menguji hubungan antara variabel. Hasil penelitian menunjukkan bahwa Work Life Balance dan Self Efficacy memiliki hubungan positif yang sangat signifikan dengan Organizational Citizenship Behavior (R = 0,694, p < 0,05). Secara keseluruhan, penelitian ini menyarankan agar perusahaan dapat mempertahankan lingkungan kerja yang positif agar tingkat Work Life Balance, Self Efficacy, dan Organizational Citizenship Behavior pada kalangan pekerja tetap tinggi.Kata kunci: Organizational Citizenship Behavior, Self Efficacy, Work Life Balance